Elevated Oxidative Stress and Inflammation in Hypothalamic Paraventricular Nucleus Are Associated With Sympathetic Excitation and Hypertension in Rats Exposed to Chronic Intermittent Hypoxia - Li, Tiejun; Chen, Yanli; Gua, Chaojun; Wu, Baogang (Frontiers in Physiology, 2018)
Obstructive sleep apnea (OSA), characterized by recurrent collapse of the upper airway during sleep leading to chronic intermittent hypoxia (CIH), is an independent risk factor for hypertension. Sympathetic excitation has been shown to play a major role in the pathogenesis of OSA-associated hypertension. Accumulating evidence indicates that oxidative stress and inflammation in the hypothalamic paraventricular nucleus (PVN), a critical cardiovascular and autonomic center, mediate sympathetic excitation in many cardiovascular diseases. Here we tested the hypothesis that CIH elevates oxidative stress and inflammation in the PVN, which might be associated with sympathetic excitation and increased blood pressure in a rat model of CIH that mimics the oxygen profile in patients with OSA. Sprague-Dawley rats were pretreated with intracerebroventricular (ICV) infusion of vehicle or superoxide scavenger tempol, and then exposed to control or CIH for 7 days. Compared with control+vehicle rats, CIH+vehicle rats exhibited increased blood pressure, and increased sympathetic drive as indicated by the blood pressure response to ganglionic blockade and plasma norepinephrine levels. Pretreatment with ICV tempol prevented CIH-induced increases in blood pressure and sympathetic drive. Molecular studies revealed that expression of NAD(P)H oxidase subunits, production of reactive oxygen species, expression of proinflammatory cytokines and neuronal excitation in the PVN were elevated in CIH+vehicle rats, compared with control+vehicle rats, but were normalized or reduced in CIH rat pretreated with ICV tempol. Notably, CIH+vehicle rats also had increased systemic oxidative stress and inflammation, which were not altered by ICV tempol. The results suggest that CIH induces elevated oxidative stress and inflammation in the PVN, which lead to PVN neuronal excitation and are associated with sympathetic excitation and increased blood pressure. Central oxidative stress and inflammation may be novel targets for the prevention and treatment of hypertension in patients with OSA.